A method of Reflexive Balancing in a Pragmatic, Interdisciplinary and Reflexive Bioethics. (28th February 2013) - Ives, Jonathan
Abstract In recent years there has been a wealth of literature arguing the need for empirical and interdisciplinary approaches to bioethics, based on the premise that an empirically informed ethical analysis is more grounded, contextually sensitive and therefore more relevant to clinical practice than an 'abstract' philosophical analysis. Bioethics has (arguably) always been an interdisciplinary field, and the rise of 'empirical' (bio)ethics need not be seen as an attempt to give a new name to the longstanding practice of interdisciplinary collaboration, but can perhaps best be understood as a substantive attempt to engage with the nature of that interdisciplinarity and to articulate the relationship between the many different disciplines (some of them empirical) that contribute to the field. It can also be described as an endeavour to explain how different disciplinary approaches can be integrated to effectively answer normative questions in bioethics, and fundamental to that endeavour is the need to think about how a robust methodology can be articulated that successfully marries apparently divergent epistemological and metaethical perspectives with method. This paper proposes 'Reflexive Bioethics' (RB) as a methodology for interdisciplinary and empirical bioethics, which utilizes a method of 'Reflexive Balancing' (RBL). RBL has been developed in response to criticisms of various forms of reflective equilibrium, and is built upon a pragmatic characterization of Bioethics and a 'quasi‐moral foundationalism', which allows RBL to avoid some of the difficulties associated with RE and yet retain the flexible egalitarianism that makes it intuitively appealing to many.